5.0k views
3 votes
Find the equations for the asymptotes of the hyperbola.

Find the equations for the asymptotes of the hyperbola.-example-1

1 Answer

3 votes

Answer:


y = (3)/(4) x \: \: and \: \: y = - (3)/(4) x

Explanation:

The given hyperbola has equation:


\frac{ {x}^(2) }{16} - \frac{ {y}^(2) }{9} = 1

The equations of asymptotes of the hyperbola.


\frac{ {x}^(2) }{ {a}^(2) } - \frac{ {y}^(2) }{ {b}^(2) } = 1

is


y = \pm \: (b)/(a) x

Comparing the given equation to the standard equation of the hyperbola we have:


\frac{ {x}^(2) }{ {4}^(2) } - \frac{ {y}^(2) }{ {3}^(2) } = 1

This implies that:

a=4 and b=3

The asymptote equations are:


y = \pm (3)/(4)x

Or


y = (3)/(4) x \: \: and \: \: y = - (3)/(4) x

User Venko
by
5.4k points